EVALUASI PROGRAM PEKARANGAN PANGAN LESTARI (P2L) KELOMPOK WANITA TANI DI KOTA BOGOR - Sukmawati, Ellies; Syamsiah, Siti (Social Welfare Study Program, 2024)
Abstract. P2L is a productive activity that empowers the community, especially housewives so that they are able to meet the availability of family food while supporting the household economy, but in its implementation, there are obstacles that prevent P2L from achieving its goals. The purpose of the study was to evaluate the performance of the P2L program based on aspects of inputs, outputs and outcomes in the Mekar Saluyu Farmer Women's Group (KWT) located in Bogor City. The evaluation of this P2L program uses a logic model with a quantitative approach and descriptive analysis of research data. The evaluation results stated that KWT Mekar Saluyu has implemented the P2L program well, this is indicated by an increase in knowledge, skills and attitudes of KWT members to optimize yard land management for P2L activities so that it has an impact on reducing spending on vegetables because it has been fulfilled from P2L results, but limited arable land area results in vegetable production capacity is not optimal.Keywords: P2L, KWT, evaluation of logic model. Abstrak. P2L merupakan kegiatan produktif yang memberdayakan masyarakat, khususnya ibu-ibu rumah tangga agar mereka mampu mencukupi ketersediaan pangan keluarga sekaligus menunjang ekonomi rumah tangga, namun dalam pelaksanaannya terdapat kendala yang menghambat P2L mencapai tujuannya. Tujuan penelitian adalah mengevaluasi kinerja program P2L berdasarkan aspek input, output dan outcome di Kelompok Wanita Tani (KWT) Mekar Saluyu yang berada di Kota Bogor. Evaluasi program P2L ini menggunakan logic model dengan pendekatan kuantitatif dan analisis deskriptif terhadap data penelitian. Hasil evaluasi menyebutkan KWT Mekar Saluyu telah melaksanakan program P2L dengan baik, ditandai dengan peningkatan pengetahuan, keterampilan dan sikap anggota KWT mengoptimalkan pengelolaan lahan pekarangan untuk kegiatan P2L sehingga berdampak kepada berkurangnya pengeluaran belanja untuk sayuran karena telah terpenuhi dari hasil P2L, namun keterbatasan luas lahan garapan mengakibatkan kapasitas produksi sayuran belum optimal. Kata Kunci: P2L, KWT, evaluasi logic model.